PRACTITIONER'S PERFORMANCE IN A LECTURING AS THE NEW EFFORT STUDENTS’ READINESS FOR THE WORK PLACE - Sumarni; Marjoni Rachman; Legowo Kamarubayana; Nanik Pujiastuti; M.Ibnu Ashari.R; Danial (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
The teaching Practitioner is a program initiated by the Ministry of Education,Culture, Research and Technology of Indonesia , collaborate practitioner and lecturer in a classroom of a university so that college graduates are better prepared to enter the world place. In this study wants to know performances of the practitioner by getting students’ impression reflected in their choices of a questioner. Descriptive approach was used to analyze 19 students’ answering in order to describe many practitioners’ performances as an effort students’ readiness in a work place. The result of this study reach out the justification that this program is very good in supporting students’ willingness become be minded in work place.